Rice cultivars response to phosphorus in nutrient solution - Fageria, Nand Kumar (2014)
Due to widespread deficiency of phosphorus in acid soils in various parts of the world, germplasm screening for identification of less susceptible cultivars of crop plants has become as essential as recommendation of proper methods and levels of P fertilization. To study the relationship between differential susceptibility to P deficiency, four cultivars of rice (Oryza sativa L.) were grown in nutrient solution at 8.06, 32.25, 322.58 μM (0.25, 1 and 10 μg P.ml-1) of applied P. After 54 days of growth in nutrient solution, dry matter yield of roots and shoots and P and K uptake were measured. Rice cultivars did not differ widely in dry matter production and P uptake. Among the growth parameters, shoot dry weight was the best parameter for classifying cultivars as to P efficiency. Based on this parameter, cultivars were classified for P efficiency in the order: IRAT 104 > Beira Campo > Bico Torto > Quatro Meses. Phosphorus uptake was increased with increasing concentrations of P in the growth medium. This study suggests that this methodology can be used for identification of P efficient rice cultivars.